Strategi Pemasaran Dana Pensiun dalam Meningkatkan Pruduk Pensiun pada Bank BSI KCP Jember Gajah Mada - Zakiyatur Razinah; Uly Aunil ‘Asyura; Mohammad Daud Rosyidi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The purpose of this study was to determine how the marketing strategy of Islamic pension fund products at Bank Syariah Indonesia and what obstacles are faced when marketing pension fund products to the people of Indonesia, This marketing strategy is structured based on what to do, who does it, and when to do it. The marketing strategy used by Bank Syariah Indonesia KCP Jember Gajah Mada in increasing sales of pension products is to use promotional approaches and strategies. This approach to customers can increase the long-term growth of Bank Syariah Indonesia KCP Jember Gajah Mada and maximum customer satisfaction. After conducting the approach process, the next stage is the promotion strategy. Promotion is an activity that aims to convey information about pension products to customers, so that these pension products are known and can encourage customers to use them. Promotion is also very useful for providing information about the advantages or disadvantages of these pension products. The method used in this research is a qualitative research method, namely by making observations to the research location, conducting interviews with Bank Syariah Indonesia employees and collecting data from various sources related to this research. It is hoped that from the results of this research, Bank Syariah Indonesia can market its products in accordance with the wishes of the Indonesian people who make transactions safely, comfortably and blessedly.